Effects of nonlinear resistance training and supplementation of licorice on blood lipoprotein profile in overweight untrained young men - H Naghizadeh; MA Azarbayjani; M Peeri; H Matinhomaee (Institue of Medicinal Plants, ACECR, 2016)
Background: Strengthening endogenous antioxidant body system and reduction lipid peroxidation people exposed metabolic syndrome by using resistance training along with herbal supplements is important research topics in the field of health, but in this area are still numerous questions remain unanswered. Objective: The aim of this study was to the effect of nonlinear resistance training and supplementation of licorice on the blood lipoprotein profile in overweight untrained young men. Methods: In a double-blind trial quasi-experimental design, 48 healthy young men overweight by using simple random sampling and were divided into six groups of 8: Nonlinear resistance training with 250 mg of licorice supplementation, Nonlinear resistance training with 500 mg of licorice supplementation, 250 mg of licorice supplementation, Nonlinear resistance training with 250 mg of placebo and Control with 250 mg of placebo. Exercise program was carried out 3 times a week for 8 weeks. Before and after the end of the last training session were measured functional characteristics and anthropometric along with blood samples to measure lipoprotein profile. Results: After 8 weeks, highest percentage of significant changes in serum levels of HDL-C (-10.22 %) observed in the nonlinear resistance training with dose of 500 mg of licorice supplementation. Conclusion: It is suggested, use of licorice along with nonlinear resistance training could be an effective therapy for favorable changes in the lipoprotein profile and reduction start the process of arteriosclerosis.